The Library of Parliament’s Competency-Based New-Librarian Development Program - Fraser-Arnott, Melissa; Martyn, Maureen (Partnership, 2023)
Employee orientation and development are essential organizational processes. This paper examines a competency-based new-librarian development program in a legislative library setting, emphasizing program redesign and continuous improvement. The new-librarian development program was originally introduced in 2012 and was revised in 2018 in response to changes in the organization’s structure, the introduction of a revised competency framework and feedback from stakeholders. The new-librarian development program uses recommended practices from the employee development literature as a frame. The process of developing and redesigning the program offers insights into how librarians can develop customized development programs. A copy of the competency profile for research librarians is included in the appendix.